13: a novel - Robert Brown, Jason; Elish, Dan (2022. Harper Collins)
Almost thirteen-year-old Evan Goldman learns what it means to be a man when his parents separate and he and his mother move from New York City to Appleton, Indiana, right before his bar mitzvah.
Keywords: Divorce Fiction; Schools Juvenile fiction; Peer pressure Fiction